Stenotrophomonas in diversified cropping systems: friend or foe? - Kumar, Abhishek; Rithesh, Lellapalli; Kumar, Vikash; Raghuvanshi, Nikhil; Chaudhary, Kautilya; Abhineet,; Pandey, Abhay K. (Frontiers in Microbiology, 2023)
In the current scenario, the use of synthetic fertilizers is at its peak, which is an expensive affair, possesses harmful effects to the environment, negatively affecting soil fertility and beneficial soil microfauna as well as human health. Because of this, the demand for natural, chemical-free, and organic foods is increasing day by day. Therefore, in the present Stenotrophomonas in plant growth promotion and management of pests and diseases under diverse growth conditions and to demonstrate its interaction with plant and soil systems. The present review discusses various plant growth and biocontrol attributes of the genus Stenotrophomonas in various food crops along with knowledge gaps. Additionally, the potential risks and challenges associated with the use of Stenotrophomonas in agriculture systems have also been discussed along with a call for further research in this area.